Afrodescendência, memória e tecnologia: uma aplicação do conceito de informação etnicorracial ao projeto “A Cor da Cultura” - Oliveira, Henry Poncio Cruz de (2010)
Contemporary society has set as learning society or network society is characterized by constant evolution of intellectual technologies so that the production of information and knowledge has a fundamental role. This context has motivated this study: to analyze the project ‘The Color justifying of Culture’ (PACC), considering the relationship afrodescendant, information, memory and technology; develop a concept of ethnic and racial information cultural production that represents the afrodescendant in perspective to reduce prejudice, discrimination and racism in the learning society; apply the concept by PACC and to analyze the informational production organized and available for access and use. From the qualitative approach and the hermeneutic dialectical epistemology, this study used the methodological bricolage to support to articulate Discourse Analysis, Semiotics from Peirce and Digital Information Architecture as analytical possibilities as applicable orders discursive, media and technology of PACC. The concept of ethnic and racial information was systematized from the Theory of Meaning and theoretically connected to the memory of African descent. This study enabled us to see PACC as a producer of information etnicorracial with clipping of African descent and investigate how this information is structured to build the memory of African descent.